Characteristics of Respiratory Syncytial Virus versus Influenza infection in hospitalized patients of Peru: a retrospective observational study - Ramírez Soto, Max Carlos (2022)
Respiratory syncytial virus (RSV) and influenza infections are important causes of respiratory illness associated with hospitalizations in children in Peru; however, comparisons of RSV and influenza hospitalization across all age groups are not available in Peru. Therefore, we conducted an observational, retrospective study between May 2015 and October 2021 using hospitalization from RSV and influenza infection data obtained from SUSALUD (open data) in Peru to compare the baseline characteristics of sex, age, region, and infection type. For the study, 2696 RSV-infected and 1563 influenza-infected hospitalized patients from different age groups were included. Most hospitalizations from RSV infection and the influenza virus occurred in children <5 years of age (86.1% vs. 32.2%, respectively). Compared with influenza infection, RSV infection was less likely to occur in individuals ≥5 years of age (adjusted odds ratio (aOR) = 0.07; 95% confidence interval (CI), 0.06–0.08; p < 0.0001; compared to <5 years of age), and more likely to occur in highlands (aOR = 1.75; 95% CI, 1.46–2.07; p < 0.0001, compared to coast region), and jungle region (aOR = 1.75; 95% CI, 1.27–2.41; p = 0.001, compared to coast region). Among the respiratory complications, RSV pneumonia was less likely to occur between different age groups (aOR = 0.29; 95% CI, 0.22–0.37; p < 0.0001, compared to <5 years of age), compared with influenza pneumonia. These findings on the RSV-hospitalization and its complications are helpful for health services planning and may increase awareness of the Peruvian population’s RSV and influenza disease burden.